Asprellcosides B of Ilex asprella Inhibits Influenza A Virus Infection by Blocking the Hemagglutinin- Mediated Membrane Fusion - Zhang, Wen; Chen, Si-Tai; He, Qiu-Yan; Huang, Li-Quan; Li, Xiong; Lai, Xiao-Ping; Zhan, Shao-Feng; Huang, Hui-Ting; Liu, Xiao-Hong; Wu, Jianguo; Li, Geng (Frontiers in Microbiology, 2019)
INTRODUCTION: Ilex asprella is a herbal drug commonly used to treat influenza (Flu) in Traditional Chinese Medicine. The study aims to identify the distinct molecular mechanism of the triterpenoid of Ilex asprella in anti-influenza process against influenza A virus H1N1. METHODS: Anti-influenza A virus activity of Asprellcosides B were evaluated by classical antiviral experiments. Structural modeling was used to predict the target of the compound. The Surface plasmon resonance (SPR) assay was applied to identify the interaction between the compound and viral proteins. RESULTS: Asprellcosides B displayed a low toxicity in confluent A549 cell monolayers with a median toxic concentration (TC50) > 250 µM. Asprellcosides B had an antiviral activity with inhibition ratio of 63.13%, selection index (SI) of 28.18 µM, and half maximal inhibitory concentration (IC50) value of 8.87 µM. Asprellcosides B had no inhibitory effect on hemagglutinin (HA) activity in the inhibition of hemagglutinin assays, while the drug’s inhibition ratio was 70.83% at the highest level of viral content in the inhibition of hemolysis assays. Molecular docking simulation displayed a high probability of the binding between Asprellcosides B and HA2. Finally, SPR analyses showed that there was a kinetic affinity between Asprellcosides B and HA protein with a KD value of 7.44 µM. CONCLUSIONS: Our results suggested that Asprellcosides B displayed anti-influenza A virus activity. This study revealed a molecular mechanism by which Asprellcosides B binds to the hydrophobic pocket of HA2 to inhibit the membrane fusion of virion and the host cell, thereby attenuating the virus replication.